The Assessment of Distortion in Neurosurgical Image Overlay Projection. (February 2016) - Vakharia, Nilesh N.; Paraskevopoulos, Dimitris; Lang, Jozsef; Vakharia, Vejay N.
Background . Numerous studies have demonstrated the superiority of neuronavigation during neurosurgical procedures compared to non-neuronavigation-based procedures. Limitations to neuronavigation systems include the need for the surgeons to avert their gaze from the surgical field and the cost of the systems, especially for hospitals in developing countries. Overlay projection of imaging directly onto the patient allows localization of intracranial structures. A previous study using overlay projection demonstrated the accuracy of image coregistration for a lesion in the temporal region but did not assess image distortion when projecting onto other anatomical locations. Our aim is to quantify this distortion and establish which regions of the skull would be most suitable for overlay projection. Methods . Using the difference in size of a square grid when projected onto an anatomically accurate model skull and a flat surface, from the same distance, we were able to calculate the degree of image distortion when projecting onto the skull from the anterior, posterior, superior, and lateral aspects. Measuring the size of a square when projected onto a flat surface from different distances allowed us to model change in lesion size when projecting a deep structure onto the skull surface. Results . Using 2 mm as the upper limit for distortion, our results show that images can be accurately projected onto the majority (81.4%) of the surface of the skull. Conclusion . Our results support the use of image overlay projection in regions with ≤2 mm distortion to assist with localization of intracranial lesions at a fraction of the cost of existing methods.